Apolipoprotein A-I directly interacts with extracellular domain 1 of human ABCA1. Issue 3 (4th March 2019) - Kawanobe, Takaaki; Shiranaga, Naoko; Kioka, Noriyuki; Kimura, Yasuhisa; Ueda, Kazumitsu
ABSTRACT: ATP-binding cassette transporter A1 (ABCA1) is critical for the generation of nascent high-density lipoprotein (HDL) and plays important roles in cholesterol homeostasis. ABCA1 has two large extracellular domains (ECDs), which may interact directly with apolipoprotein A-I (apoA-I). However, the molecular mechanisms underlying HDL formation and the importance of ABCA1–apoA-I interactions in HDL formation remain unclear. We investigated the ABCA1–apoA-I interaction in photo-activated crosslinking experiments using sulfo-SBED–labeled apoA-I. ApoA-I bound to cells expressing ABCA1, but not to untransfected cells or cells expressing non-functional ABCA1. Binding was inhibited by sulfo-SBED–labeled apoA-I, and crosslinking of sulfo-SBED–labeled apoA-I with ABCA1 was inhibited by non-labeled apoA-I, suggesting that sulfo-SBED–labeled apoA-I specifically binds and crosslinks with functional ABCA1. Proteolytic digestion of crosslinked ABCA1 revealed that apoA-I bound the N-terminal half of ABCA1, and that the first ECD of ABCA1 is an apoA-I binding site. Abbreviations : ABC: ATP-binding cassette; apoA-I: apolipoprotein A-I; ATP: adenosine triphosphate; CHAPS: 3-(3-cholamidepropyl)dimethylammonio-1- propanesulphonate; DTT: dithiothreitol; ECD: extra cellular domain; EDTA: ethylenediaminetetraacetic acid; GFP: green fluorescent protein; HA: hemagglutinin; HDL: high density lipoprotein; HEK: human embryonic kidney; HEPES: 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid; sulfo-SBED: (sulfosuccinimidyl-2-[6-(biotinamido)-2-(p-azidobenzamido)hexanoamido] ethyl-1, 3ʹ-dithiopropionate; NHS-ester, N-hydroxysuccinimide-ester Graphical abstract: : ABCA1 directly interacts with apoA-I with its first extracellular domain for generating nascent HDL.